Does more general education reduce the risk of future unemployment? Evidence from labor market experiences during the Great Recession - Caroline Hall (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2013)
This paper investigates whether more general education reduces the risk of future unemployment by examining individuals' labor market experiences during the Great Recession (2008-2010). To estimate the causal impact of differences in educational content, I exploit a reform in Sweden in the 1990s which prolonged vocational programs in upper secondary school and gave them a considerably larger general content. The research design takes advantage of variation across regions and over time in the implementation of a large-scale pilot which preceded the reform. I find no evidence that having attended a longer and more general program reduced the risk of experiencing unemployment during the 2008-2010 recession. Among students with low GPAs from compulsory school, attending a pilot program seems instead to have led to an increased risk of unemployment. This pattern is strongest among male students and the effect is likely to be explained by the increased dropout rate which resulted from the change of the programs.
Keywords: I21; I28; 330; vocational education; upper secondary school curriculum; unemployment